Coris sandageri, an unjustified emendation of Coris sandeyeri (Hector 1884) (Pisces, Labridae) - Russell, Barry C. (Zootaxa, 2011)
Confusion has surrounded the correct spelling of the species name of the labrid fish Cymolutes (=Coris) sandeyeri Hector 1884. In his original description, Hector (1884a) stated the specimen from Tiritiri Island was “collected by Mr. S. Sandeyer”, a misspelling of the surname of F.S. (Andreas Fremming Stewart) Sandager, who was then Assistant Lighthouse Keeper at Tiritiri Matangi Island, Hauraki Gulf, New Zealand, from June 1881 to May 1883 (Phillips 2011), and after whom the species was named.